2018
DOI: 10.1111/tmi.13141
|View full text |Cite
|
Sign up to set email alerts
|

Association of intestinal pathogens with faecal markers of environmental enteric dysfunction among slum‐dwelling children in the first 2 years of life in Bangladesh

Abstract: ObjectiveEnvironmental Enteric Dysfunction (EED) can be assessed by faecal biomarkers such as Myeloperoxidase (MPO), Neopterin (NEO) and Alpha‐1 anti‐trypsin (AAT). We aimed to test the association of intestinal pathogens with faecal markers of EED among slum‐dwelling children in first 2 years of life.MethodsThe MAL‐ED birth cohort data of Bangladesh site were used to conduct this analysis. Multivariable analyses using Generalized Estimating Equations (GEE) were performed to test the association between intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 52 publications
(68 reference statements)
1
42
0
Order By: Relevance
“…The worst symptoms of Giardia infection are associated with damage to the absorptive small intestine mucosa, along with an impaired intestinal immunity that contributes to chronic infection. Recently published data from children in Bangladesh suggested a correlation between giardiasis and increased the risk of intestinal permeability as well as an immune defect (35,37,38). Although an observation by Scott et al showed that small intestinal gut permeability increased of Giardia infected mice without any morphological damage to the intestinal mucosa, which is independent of T-cell and is secondary to reorganization of cytoskeletal F-actin and tight-junction ZO-1 protein (70).…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The worst symptoms of Giardia infection are associated with damage to the absorptive small intestine mucosa, along with an impaired intestinal immunity that contributes to chronic infection. Recently published data from children in Bangladesh suggested a correlation between giardiasis and increased the risk of intestinal permeability as well as an immune defect (35,37,38). Although an observation by Scott et al showed that small intestinal gut permeability increased of Giardia infected mice without any morphological damage to the intestinal mucosa, which is independent of T-cell and is secondary to reorganization of cytoskeletal F-actin and tight-junction ZO-1 protein (70).…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Additionally an observational study of Bangladeshi infants of an urban area indicated giardiasis was associated with the intestinal barrier disruption (38). Furthermore, another prospective longitudinal study con rmed that giardiasis was signi cantly associated with concentrations of fecal myeloperoxidase (MPO) and alpha-1-anti-trypsin (AAT) in children under the age of 2 and was also signi cantly associated with score of environmental enteric dysfunction (EED) (37). Most of these studies showed evidence that giardiasis was associated with intestinal permeability.…”
Section: Giardiasis and Poor Child Growthmentioning
confidence: 97%
“…Environmental Enteric Dysfunction (EED), an asymptomatic small intestinal pathology, has been implicated in linear growth failure of children less than two years of age [14,22]. EED is characterized by persistent immune activation, gut inflammation and altered intestinal permeability resulting from chronic exposure to intestinal pathogens and frequent enteric infections [23][24][25]. The overall negative impact of EED on child growth and development, especially in their early years of life, is now well established [22,26].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Myeloperoxidase (MPO), a marker of neutrophil activity in intestinal mucosa, and lipocalin-2 (LCN-2), a glycoprotein upregulated in tissue damage under infection conditions, have been considered as biomarkers of environmental enteric dysfunction, including EPEC, in children [35][36][37][38]. To ensure that our EPEC infection model mimics the alterations of these biomarkers as observed in children, we measured MPO and LCN-2 in the ileal and colonic tissues, as well as in cecal contents and stools.…”
Section: Epec Infection Promotes Acute Intestinal Tissue Damage and Imentioning
confidence: 99%